Study of the effect of a drug from the macromycetes Ganoderma lucidum on the phagocytic activity of peripheral blood neutrophils in patients with year-round allergic rhinitis - Bohdanov, V.; Gushcha, S. (Journal of Education, Health and Sport, 2024)
Modern complex therapy of patients with persistent (year-round, chronic) allergic rhinitis (AR), based on the use of antihistamines and intranasal glucocorticosteroids, in many cases is not effective enough, since drug therapy acts only on individual links in the pathogenesis, without preventing the progression of the allergic disease. At the same time, the quantitative and reserve capabilities of neutrophil granulocytes are depleted, which increases the level of antigenic load in patients with AR. The aim of this study is to investigate the phagocytic activity of neutrophils in patients with AR who received basic therapy and patients who received basic therapy and a course of the drug from the macromycetes Ganoderma lucidum "Astmagan". We examined 40 patients of both sexes with AR, the duration of the disease ranged from 6 months to 2 years. Patients were divided into 2 equal groups: The 1st group consisted of patients who received basic therapy (oral Loratadine and intranasal Nasonex). The 2nd group consisted of patients who received basic therapy and a course of "Astmagan". The treatment course lasted 90 days. The control group consisted of 25 healthy individuals. After the treatment, patients in both groups showed a statistically significant positive dynamics of phagocytic system activity: in group 1, the phagocytic index (FI) increased by 30 % (p=0.001), in the second group this indicator reached the normal level. Also, in patients of group 1, the phagocytic number (PN) increased by 35 % (p=0.0001), but did not reach the normal level. According to the results of comparative evaluation, a greater efficacy of the treatment complex with the additional use of "Astmagan" was established, which is manifested in the restoration of phagocytic activity of peripheral blood neutrophils, the effect persists for 6 months after treatment.